2013
DOI: 10.4239/wjd.v4.i2.27
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and renal tubular cell apoptosis

Abstract: Apoptosis contributes to the development of diabetic nephropathy, but the mechanism by which high glucose induces apoptosis is not fully understood. Apoptosis of tubular epithelial cells is a major feature of diabetic kidney disease, and hyperglycemia triggers the generation of free radicals and oxidant stress in tubular cells. Hyperglycemia and high glucose in vitro also lead to apoptosis, a form of programmed cell death. High glucose similar to those seen with hyperglycemia in people with diabetes mellitus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 45 publications
4
50
0
Order By: Relevance
“…Forty-five proteins (~15.5% of all proteins in MetBridge DKD ) in the subnetwork had GO annotation of "regulation of apoptosis", which was identified as a significantly enriched GO term (Benjamini-Hochberg corrected P value < 0.0484). Previous studies have shown that high glucose induces apoptosis in various cells including podocytes and tubular epithelial cells, which both contribute to development of diabetic kidney disease (18). The subnetwork of MetBridge DKD , which consists of bridge proteins involved in regulation of apoptosis, their interacting enzymes and metabolites associated with them, are shown in Figure 2A.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-five proteins (~15.5% of all proteins in MetBridge DKD ) in the subnetwork had GO annotation of "regulation of apoptosis", which was identified as a significantly enriched GO term (Benjamini-Hochberg corrected P value < 0.0484). Previous studies have shown that high glucose induces apoptosis in various cells including podocytes and tubular epithelial cells, which both contribute to development of diabetic kidney disease (18). The subnetwork of MetBridge DKD , which consists of bridge proteins involved in regulation of apoptosis, their interacting enzymes and metabolites associated with them, are shown in Figure 2A.…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis is a form of programmed cell death characterized by cell shrinkage, chromatin condensation, and DNA fragmentation in a variety of cell types, including renal proximal tubular epithelial cells. 13,14 The mechanisms by which hyperglycemia promotes apoptosis in renal tubular cells are poorly understood. Previous studies have proved that oxidative stress plays a major role in DKD.…”
Section: Discussionmentioning
confidence: 99%
“…5 Hyperglycemia triggers the generation of free radicals in various cells of the kidney, including proximal tubular epithelial cells, and consequently proliferation, extracellular matrix deposition, and apoptosis emerge. 6 The mechanisms by which hyperglycemia leads to tubular cell apoptosis are not completely understood. Recently, the mitochondrion has emerged as a major source of reactive ROS and UCP2, a mitochondrial membrane protein, has been reported to participate in the regulation of ROS generation.…”
Section: Introductionmentioning
confidence: 99%
“…5 A ). To further test the physiologic relevance of this finding, primary proximal tubule cells were also exposed to high glucose, a well-known trigger of apoptosis and a major mediator of diabetic complications (60). Ouabain protects from apoptosis cells exposed to high glucose but not cells exposed to high glucose where CAMK2G was down-regulated (Fig.…”
Section: Resultsmentioning
confidence: 99%